2022
DOI: 10.3390/biom12111572
|View full text |Cite
|
Sign up to set email alerts
|

Importance of TGFβ in Cancer and Nematode Infection and Their Interaction—Opinion

Abstract: Historically, there has been little interaction between parasitologists and oncologists, although some helminth infections predispose to the development of tumours. In addition, both parasites and tumours need to survive immune attack. Recent research suggests that both tumours and parasites suppress the immune response to increase their chances of survival. They both co-opt the transforming growth factor beta (TGFβ) signalling pathway to modulate the immune response to their benefit. In particular, there is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…Helminths are strong modulators of the host milieu. Studies on the transforming growth factor beta (TGF-β) confirmed that immune response to helminths is strongly dependent on both host and parasite factors [ 20 ]. Neutralization of TGF-β affected the concentration of cytokines and their pattern of production and resulted in a reduction in worm numbers and fecal egg counts [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Helminths are strong modulators of the host milieu. Studies on the transforming growth factor beta (TGF-β) confirmed that immune response to helminths is strongly dependent on both host and parasite factors [ 20 ]. Neutralization of TGF-β affected the concentration of cytokines and their pattern of production and resulted in a reduction in worm numbers and fecal egg counts [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to identify the neuroregulatory pathways induced by infection with intestinal nematodes. However, these studies suggest that treatment of immune disorders caused by nematode infection must be completed with caution, especially in elderly patients, because their immune response is slower and may cause pathogenesis in the nervous tissue [ 96 ]. Given the increasing burden of neurodegenerative diseases, understanding such connections could have important implications for health strategies to improve health and prevent dementia in ageing human populations.…”
Section: Discussionmentioning
confidence: 99%
“…Murine infections have helped to elucidate some mechanisms involved in helminth therapy. Furthermore, the effects of H. polygyrus -derived molecules are not limited to mice but also affect human cells [ 9 ]. Therefore, H. polygyrus may similarly influence an immune response in humans.…”
Section: Introductionmentioning
confidence: 99%